2013
DOI: 10.1111/dmcn.12317
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of gross motor function of young children with cerebral palsy: a prospective cohort study

Abstract: AIM The aim of this study was to test a model of determinants of gross motor function of young children with cerebral palsy (CP).METHOD Four hundred and twenty-nine children with CP (242 males, 187 females; mean age 3y 2mo, SD 11mo) representing all levels of the Gross Motor Function Classification System (GMFCS) participated. Children in levels I to II and III to V were classified as Groups 1 and 2 respectively. Distribution of CP was quadriplegia, 44%; hemiplegia, 24%; diplegia, 23%; triplegia, 6%; and monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 27 publications
(47 reference statements)
4
36
2
Order By: Relevance
“…61 A fourth focus of intervention could be increasing infants' adaptive behaviors, motivation, and persistence so that they are more driven to move and explore. 52 A fifth focus of inter-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 A fourth focus of intervention could be increasing infants' adaptive behaviors, motivation, and persistence so that they are more driven to move and explore. 52 A fifth focus of inter-…”
Section: Discussionmentioning
confidence: 99%
“…For instance, for many children with cerebral palsy, those better able to adapt their behaviors for activities of daily living also tend to have better motor function. 52 This finding may reflect the fact that those children have higher levels of intrinsic characteristics, such as self-awareness, adaptability, motivation, problem solving, persistence, and risk taking. The differences in exploratory behaviors also may be the result of differences in extrinsic characteristics, such as caregiving in environments that offer different quantities and qualities of interactions with people and objects.…”
Section: Variability Of Exploratory Behavior In Infants Born Preterm mentioning
confidence: 99%
“…There are a great variety of training interventions used by therapists to improve motor function by identifying and modifying deficits in the child's motor system. A number of studies have shown a significant relationship between motor function and various impairments such as spasticity, quality of movement, postural stability, distribution of involvement, strength, range of motion limitations, and reduced endurance . A review of the assessment of postural control in children with CP concluded that a link between postural control and functionality was evident but that there was a lack of studies assessing postural control by means of scales and functional tests or during daily functional activities .…”
mentioning
confidence: 99%
“…Percentage agreement for levels I and II versus III, IV, and V (i.e. the same functional dichotomy used in previous work 4,5 ) was higher for the more functional group (levels I and II) by 1.1% (GMFCS), 2% (MACS) and 4% (CFCS), with only the CFCS reaching statistical significance (v 2 =4.62, df=1, p=0.03). We generated guidelines to reconcile disagreements for research purposes.…”
mentioning
confidence: 59%
“…In previous work, we established an understanding of the child, family, and service factors that contribute to motor development, 4 self-care, 5 and participation (under review) of two functionally distinct subgroups of children with CP. To assist with planning for individualized care to optimize these outcomes, the next stage in our research is to describe the developmental trajectories (both longitudinal growth and centile curves) of change in balance, limitations of range of motion, strength and endurance, and number and impact of associated health conditions, as well as participation in self-care and recreational activities.…”
mentioning
confidence: 99%